2022
DOI: 10.3390/foods11142015
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic Heating Extraction at Different Times, Temperatures, Voltages, and Frequencies: A New Energy-Saving Technique for Pineapple Core Valorization

Abstract: Pineapple core is considered a processing by-product. This study proposed and evaluated an ohmic heating extraction-based valorization platform to obtain value-added bioactive compounds from pineapple core and studied the effects of four important processing parameters. In this sense, a Taguchi design (L16(4)4) was used to assess the effects of temperature (70, 80, 90, and 100 °C), time (15, 30, 45, and 60 min), voltage (110, 160, 210, and 260 V), and frequency (60, 340, 620, and 900 Hz) on heating rate, come-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Both higher values for voltage gradient and extraction time increased the TPC at a certain point and then decreased. A recent study analyzed the effect of higher voltage and longer heating time on the phenolics from pineapple cores using ohmic heating (Gavahian & Chu, 2022 ). It was obtained that increasing the voltage up to 30 V resulted in a significant increase in phenolic extraction efficiency but increasing the voltage beyond 30 V did not result in further improvement in the extraction efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both higher values for voltage gradient and extraction time increased the TPC at a certain point and then decreased. A recent study analyzed the effect of higher voltage and longer heating time on the phenolics from pineapple cores using ohmic heating (Gavahian & Chu, 2022 ). It was obtained that increasing the voltage up to 30 V resulted in a significant increase in phenolic extraction efficiency but increasing the voltage beyond 30 V did not result in further improvement in the extraction efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic composition and amounts in avocado leaves can vary depending on different factors such as solvent and extraction type, maturity and cultivar of leaves, temperature, and extraction time (Castro‐López et al, 2019 ; Che‐Galicia et al, 2020 ). On the other hand, the fast, efficient, and significant amount of phenolic extraction from avocado leaves by OHAE could be explained by not requiring high temperatures or strong solvents and providing the destruction of the cellular matrix through electrical application to enhance the greater release of phenolic compounds (Gavahian & Chu, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these compounds are generally less stable and can be damaged by high temperatures in conventional extraction processes. Ohmic technology, which uses electric voltage, is considered more effective in maintaining active compounds' effectiveness and more capable of saving energy and processing time [47]. Other studies have demonstrated that low-energy electric fields and thermal processes can be combined and optimized to extract anthocyanins and phenolic compounds from plant tissues in a single phase.…”
Section: Ohmic Heating For Extractionmentioning
confidence: 99%
“…The pineapple processing industry generates a considerable volume of waste considering pineapple annual production statistics (about 40 Mt) and discards of its unpalatable parts (e.g., core, crown, and peel), which is about 60% of the total weight (Gavahian and Chu, 2022b;Hussain et al, 2022;OECD/FAO, 2021). Dealing with such vast agricultural waste has been an environmental challenge (Hikal et al, 2021;Samota et al, 2023).…”
Section: Introductionmentioning
confidence: 99%